The effects of cost, normative support, and issue importance on motivation to persuade In-group deviants - Daniel Frings (2010)
Persuading in-group deviants to become normative may carry costs that outweigh the advantages of group consensus. This study investigates the effects of potential cost, normative support, and issue importance on group members' efforts to change the views of in-group deviants (N = 115). In line with previous research into bystander intervention, the authors show that when costs are low, high levels of either importance or normative support are sufficient to increase persuasion action tendency. When costs are higher, higher levels of both issue importance and normative support are necessary to increase persuasion action tendency. In addition, content analysis of messages sent to in-group deviants show that high potential costs and low levels of issue importance reduce the proportion of messages sent that are persuasive. These results are discussed in terms of theories of approach/avoidance and social identity.